ORGANIZATIONAL CULTURE IN EDUCATIONAL INSTITUTIONS: DEFINITION, FUNCTION, FORMATION, AND LEARNING PROCESS - Safuroh; Devi Fatwanti; Zakariya Syafei; Rijal Firdaos; Eka Sri Mulyani (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2026)
Organizational culture is a crucial factor influencing the success of an organization, including educational institutions. Organizational culture reflects the values, norms, beliefs, and habits adopted by organizational members in carrying out their activities. This research aims to examine the concept of organizational culture which includes the meaning, function, process of creating and maintaining, and ways of learning organizational culture. This study used a literature review method by analyzing various scientific sources related to organizational culture. The results of the study indicate that organizational culture plays a significant role in shaping organizational identity, increasing member commitment, and directing the behavior of organizational members in achieving organizational goals. A strong organizational culture can be created through effective leadership, clear organizational values, and the instilling of positive behaviors. Furthermore, organizational culture can be learned through observation, social interaction, organizational policies, organizational training, and work experience within the organization. Therefore, good organizational culture management is crucial in improving organizational effectiveness and performance, particularly in educational institutions.